2020
DOI: 10.1111/jerd.12679
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial analysis of optical properties, sorption, and solubility of sculptable universal composites for enamel layering upon staining in colored beverages

Abstract: Objective To analyze the effects of factors 'composite,' 'medium,' and 'time' on color, translucency, and sorption/solubility of sculptable universal composites for enamel layering upon immersion in colored beverages. Materials and methods Disk‐shaped specimens, 10 mm in diameter and 2 mm thick (n = 5/group), of ultrafine, hybrid composite Essentia (GC), microhybrid Gaenial Anterior (GC), nanofilled Filtek Ultimate Enamel and Body ( 3M ESPE) were immersed in red wine, coffee, or distilled water for 15 days. CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Protective PVP-VA coating may also be the reason for a different staining pattern in composites (and glass ionomer), i.e. the lack of progressive increase in staining over time, which was previously reported in other staining scenarios 30 , 31 . It is generally known that staining of dental restorative materials has an extrinsic and intrinsic component, the former occurring due to pigment adsorption on material surface and the latter due to absorption of pigments and internal structural changes in the polymer.…”
Section: Discussionmentioning
confidence: 71%
“…Protective PVP-VA coating may also be the reason for a different staining pattern in composites (and glass ionomer), i.e. the lack of progressive increase in staining over time, which was previously reported in other staining scenarios 30 , 31 . It is generally known that staining of dental restorative materials has an extrinsic and intrinsic component, the former occurring due to pigment adsorption on material surface and the latter due to absorption of pigments and internal structural changes in the polymer.…”
Section: Discussionmentioning
confidence: 71%
“…Any disagreement was resolved by discussion. After full text reading 178 studies 11,13–189 were included in the review (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Wine induced the greatest ΔE 00 /ΔE ab in all tested gingiva-colored-shaded materials, except IvoBase CAD, followed by coffee and artificial aging. Wine is known to one of the most potent discolorants of tooth-colored materials [17,22] which is the reason for its frequent use to screen color stability of restorative materials. Previous studies also reported comparable or higher color differences induced by red wine than coffee in gingiva-colored resin-based restorative materials [7,8,24,26] with curry being another potent discolorant for this type of materials [19].…”
Section: Methodsmentioning
confidence: 99%
“…Color stability is usually determined by immersion of samples in colored beverages, most often red wine and coffee, due to their strong staining potential. Unlike tooth-colored restorative materials [16][17][18][19][20][21][22], optical properties of gingiva-colored resinbased restorative materials have not been extensively studied. Effects of staining in various colored beverages on surface properties were evaluated for gingiva-colored composites [7,8,23] and CAD/CAM or resin-based denture base materials [24][25][26].…”
Section: Introductionmentioning
confidence: 99%